Mn(II)-Catalyzed N-Acylation of Amines - Ma, Juan; Zhang, Jingyu; Gong, Hang (Synthesis, 2019)
A practical protocol has been developed here for the Mn(II)-catalyzed N-acylation of amines with high yields using N,N-dimethylformamide and other amides as the carbonyl source. The protocol is simple, does not require any acid, base, ligand, or other additives, and encompasses a broad substrate scope for primary, secondary, and heterocyclic amines.
Keywords: synthetic methodology; N-acylation; manganese; amide; catalytic reaction